Motivators of Educational Success: Perceptions of Grade 12 Aboriginal Students - Preston, Jane P.; Claypool, Tim R. (Canadian Journal of Education/Revue canadienne de l'éducation, 2014)
The purpose of this paper is to identify motivators that support educational success, as perceived by Aboriginal high school students enrolled in two urban Saskatchewan schools. Twelve semi-structured individual interviews revealed that students were motivated by a hospitable school culture, relevant learning opportunities, and positive personal influences outside the realm of the school (e.g., family role models and Elder influence). Utilizing an Aboriginal worldview lens, student motivation stemmed from experiencing four quadrants of learning—awareness (physical), knowledge (mental), continuous improvement (emotional), and perseverance (spiritual). An implication is that educators need to incorporate features of Aboriginal pedagogy when teaching. Keywords: motivational learning, Aboriginal high school students, Aboriginal worldview